In-situ bypass is associated with superior infection-free survival compared with extra-anatomic bypass for the management of secondary aortic graft infections without enteric involvement - Janko, Matthew R.; Hubbard, Grant; Back, Martin; Shah, Samir K.; Pomozi, Eniko; Szeberin, Zoltan; DeMartino, Randall; Wang, Linda J.; Crofts, Sarah; Belkin, Michael; Davila, Victor J.; Lemmon, Gary W.; et al. (Elsevier, 2022)
Objective: The optimal revascularization modality following complete resection of aortic graft infection (AGI) without enteric involvement remains unclear. The purpose of this investigation is to determine the revascularization approach associated with the lowest morbidity and mortality using real-world data in patients undergoing complete excision of AGI. Methods: A retrospective, multi-institutional study of AGI from 2002 to 2014 was performed using a standardized database. Baseline demographics, comorbidities, and perioperative variables were recorded. The primary outcome was infection-free survival. Descriptive statistics, Kaplan-Meier survival analysis, and univariate and multivariable analyses were performed. Results: A total of 241 patients at 34 institutions from seven countries presented with AGI during the study period (median age, 68 years; 75% male). The initial aortic procedures that resulted in AGI were 172 surgical grafts (71%), 66 endografts (27%), and three unknown (2%). Of the patients, 172 (71%) underwent complete excision of infected aortic graft material followed by in situ (in-line) bypass (ISB), including antibiotic-treated prosthetic graft (35%), autogenous femoral vein (neo-aortoiliac surgery) (24%), and cryopreserved allograft (41%). Sixty-nine patients (29%) underwent extra-anatomic bypass (EAB). Overall median Kaplan-Meier estimated survival was 5.8 years. Perioperative mortality was 16%. When stratified by ISB vs EAB, there was a significant difference in Kaplan-Meier estimated infection-free survival (2910 days; interquartile range, 391-3771 days vs 180 days; interquartile range, 27-3750 days; P < .001). There were otherwise no significant differences in presentation, comorbidities, or perioperative variables. Multivariable Cox regression showed lower infection-free survival among patients with EAB (hazard ratio [HR], 2.4; 95% confidence interval [CI], 1.6-3.6; P < .001), polymicrobial infection (HR, 2.2; 95% CI, 1.4-3.5; P = .001), methicillin-resistant Staphylococcus aureus infection (HR, 1.7; 95% CI, 1.1-2.7; P = .02), as well as the protective effect of omental/muscle flap coverage (HR, 0.59; 95% CI, 0.37-0.92; P = .02). Conclusions: After complete resection of AGI, perioperative mortality is 16% and median overall survival is 5.8 years. EAB is associated with nearly a two and one-half-fold higher reinfection/mortality compared with ISB. Omental and/or muscle flap coverage of the repair appear protective.
Keywords: Antibiotic-soaked Dacron; Aortic graft infection; Axillofemoral bypass; Cryopreserved allograft; Extra-anatomic bypass; In situ bypass; Neo-aortoiliac surgery (NAIS)